The Influence of MTHFR Polymorphism on Gray Matter Volume in Patients With Amnestic Mild Cognitive Impairment - Mengzhe You (Frontiers Media S.A., 2021)
The methylenetetrahydrofolate reductase (MTHFR) gene has been associated with Alzheimer’s disease (AD) pathogenesis. Amnestic mild cognitive impairment (aMCI) represents a prodromal stage of dementia and involves a high risk of progression into AD. Although the effects of the apolipoprotein E (APOE) gene on structural alterations in aMCI have been widely investigated, the effects of MTHFR C677T and interaction effects of MTHFR × APOE genotypes on gray matter atrophy in aMCI remain largely unknown. In the present study, 60 aMCI patients and 30 healthy controls were enrolled, and voxel-based morphometry analysis was performed to inspect the effects of diagnosis, different genotypes, and their interactions on gray matter atrophy. The results showed that aMCI patients had significant gray matter atrophy involving the bilateral hippocampus, the right parahippocampal gyrus, and the left superior temporal gyrus compared with healthy controls. Besides, a substantial reduction in gray matter volume was observed in the right hippocampus region in APOE ε4 carriers from the aMCI group, compared with APOE ε4 non-carriers. A significant interaction was found between diagnosis and MTHFR C677T genotype on the right precuneus in healthy controls and aMCI patients not carrying APOE ε4 allele. Our findings may provide new evidence substantiating the genetic effects of MTHFR C677T on brain structural alternation in patients with aMCI.